IFCEE 2021 From Traditional to Emerging Geotechnics - El Mohtar, Chadi; Kulesza, Stacey; Baser, Tugce; Venezia, Michael D. (American Society of Civil Engineers, 2021)
Selected papers from the International Foundations Congress and Equipment Expo 2021, held in Dallas, Texas, May 10-14, 2021. Sponsored by the International Association of Foundation Drilling (ADSC), the Deep Foundations Institute (DFI), the Pile Driving Contractors Association (PDCA), and the Geo-Institute of ASCE.This Geotechnical Special Publication contains 40 peer-reviewed papers on the characterization of soil behavior and improvement of soil properties at multiple scales.Topics include: geotechnical earthquake engineering; nonisothermal, multiphysics behavior of soils; bioinspired, biocemented geomaterials; geostructures; and geophysical methods for site characterization.GSP 325 will be of interest to engineering practitioners, researchers, geotechnologists, contractors, and equipment manufacturers and suppliers in the deep foundation industry.
Keywords: Geotechnical engineering -- Congresses.; Soil -- Properties -- Congresses.; elektronické knihy; electronic books